105 Evidence of overtesting for venous thromboembolism in patients with COVID-19 – results of a retrospective observational multicenter study from Sweden. (8th June 2022) - Nyberg, Patrik Benjaminsson; Jörg, Matthias; Wretborn, Jens; Wilhelms, Daniel
Abstract : Objectives: Epidemiological data and studies on hospitalized patients from the beginning of the SARS-CoV-2 pandemic have shown an increased prevalence of Venous Thromboembolism (VTE) in patients with COVID19 and several guidelines advocate a higher vigilance for VTE in outpatients with COVID19. However, studies have found no increased risk of VTE when adjusting for other risk factors. As COVID19 becomes endemic, its impact on the pre-test probability for VTE needs to be established to prevent unwarranted workups for VTE in patients with COVID19. In this study we wanted to investigate the predictive value of COVID19 in patients with suspected VTE during 2020 in a whole Swedish county (Östergötland) with 465000 inhabitants. Methods: This was a retrospective observational cross-sectional study of patients within an integrated healthcare system in Sweden, covering a population of 465 000. Patients 18 years and older with a diagnostic test for VTE between 1 of January and 31 of December 2020 were included. Testing for VTE was performed with ultrasound for deep venous thrombosis (DVT) and with pulmonary angiography for pulmonary embolism (PE). COVID19 positive status was defined as a positive PCR test for SARS-CoV-2 within 14 days prior, to 7 days after testing for VTE. Risk for VTE with COVID19 was assessed by logistic regression, adjusting for risk factors such as age, sex, previous VTE, ongoing anticoagulant treatment, malignancy, Charlson score, ward care, and ICU care. Results: During 2020, 6523 patients were investigated for possible VTE of which 354 had a positive diagnosis of COVID19 around the time of investigation. The prevalence of VTE in COVID19 positive patients was 10.2% (36/354) compared to 14.7% (473/3219) in COVID19 negative patients and 15.6% (399/2589) in patients without a COVID19 test. The prevalences of PE were 10.7% (32/299), 15.6% (308/1969) and 17.4% (158/906) and the prevalences of DVT was 8.6% (5/58), 13.1% (168/1281) and 14.4% (246/1713), for COVID19 positive, negative and untested patients respectively. A COVID-positive test was not associated with an increased risk for VTE (crude odds ratio 0.64, 95%CI 0.45 - 0.91, adjusted odds ratio 0.46, 95%CI 0.19 - 1.16). Conclusions: We found no increased risk of VTE in COVID19 positive patients, suggesting that COVID19 status should not influence VTE workup. In the logistic regression analysis the odds for a VTE was lower for patients with COVID19. This is likely an indication of overtesting in this group of patients and stresses the importance of accurate pre-test assessment when considering a VTE workup in patients with COVID19 infection.